2020
DOI: 10.1021/acsenergylett.0c00872
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dimethylammonium in Bandgap Modulation for Stable Halide Perovskites

Abstract: Halide perovskites with bandgaps of 1.70–1.85 eV are of interest for multijunction photovoltaics. Mixing halides on the X site of the ABX3-structured perovskite system is a common way to reach these bandgaps, but this method introduces phase segregation pathways, limiting photovoltage. Recently, a new strategy for increasing the bandgap has been introduced, where cations normally too large to fit into the lattice, but compensated by smaller cations, are substituted on the A site. The mechanism underlying the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 42 publications
3
88
0
Order By: Relevance
“…182 Significant efforts in the field have focused on exploiting the relationship between A-site cation size, the extent of M-X-M bond angle distortion, and the overall bandgap of the system through the engineering of mixed composition MHPs. [189][190][191][192][193][194][195] For a series of MAPb(I 1-x Br x ) 3 compounds, for example, Noh and coworkers reported the ability to continuously tune the bandgap from 1.6 to 2.3 eV by increasing the value of x from 0 to 1. 196 Figure 13 displays the bandgaps of six different MHPs as a function of the X-M-X bond angle.…”
Section: Polymorph-dependent Optoelectronic Propertiesmentioning
confidence: 99%
“…182 Significant efforts in the field have focused on exploiting the relationship between A-site cation size, the extent of M-X-M bond angle distortion, and the overall bandgap of the system through the engineering of mixed composition MHPs. [189][190][191][192][193][194][195] For a series of MAPb(I 1-x Br x ) 3 compounds, for example, Noh and coworkers reported the ability to continuously tune the bandgap from 1.6 to 2.3 eV by increasing the value of x from 0 to 1. 196 Figure 13 displays the bandgaps of six different MHPs as a function of the X-M-X bond angle.…”
Section: Polymorph-dependent Optoelectronic Propertiesmentioning
confidence: 99%
“…More recent years, the dimethylammonium iodide (DAI)-related methods are widely used to stabilize the perovskite phase [29,30]. It has been reported that the incorporation of DAI into perovskite solar cells can improve the air and thermal stability as well as charge transport property [31][32][33]. Notably, the stabilization with DAI seems more promising than the use of insulating coating materials in photocatalysis because the latter may hinder the charge transfer from perovskite to surface catalytic sites and deteriorate the following redox reactions [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7d ] When the fraction of (CH 3 ) 2 NH 2 + in the A‐site of the resulting (CH 3 NH 3 ) 1− x [(CH 3 ) 2 NH 2 ] x PbI 3 film exceeds its solubility limit in the perovskite, phase separation into a (CH 3 ) 2 NH 2 + ‐rich hexagonal phase occurs. The phase separation and the structural changes introduced by undesired A‐site modifications can have a profound effect on optical properties including absorptivity [ 7d ] and bandgap, [ 20,31 ] though we only observe phase separation into the undesirable hexagonal phase at relatively low humidity exposures (30% R.H.) and over long exposure periods (>200 days). Low humidity retards degradation to PbI 2 but still facilitates the reactions that produce (CH 3 ) 2 NH 2 + .…”
Section: Discussionmentioning
confidence: 93%